О черноморском подвиде каспийского циклопа — Paracyclops ditotatus ivanegai subsp. n. (Crustacea, Copepoda) - Монченко, В.И. (Вестник зоологии, 1977)
Seven females of P. dilatatus ivanegai subsp. n. are found in the oligohaline and fresh waters of the Dniester estuary (the Black Sea basin). The illustrated description is given. The new subspecies differs from the briefly described type subspecies from the Caspian Sea in 8-segmented antennulae (the third joint has an incomplete division) and other less characteristic taxonomic characters.